2015
DOI: 10.13037/ras.vol13n45.2910
|View full text |Cite
|
Sign up to set email alerts
|

Importância Da Atenção Multidisciplinar Para Resgatar O Paciente Com Hiv/Aids Apresentando Baixa Adesão À Terapia Antirretroviral

Abstract: Introdução: No Brasil, milhares de pessoas sofrem as consequências clínicas da infecção pelo HIV, a qual é enfrentada através da distribuição gratuita de medicamentos antirretrovirais pelo Ministério da Saúde. Objetivo: Identificar, entre pacientes vivendo com HIV/AIDS em terapia antirretroviral (TARV), fatores que os levaram a não aderir ao tratamento. Material e métodos: Entre abril e novembro de 2013, foram agendados 637 pacientes para consulta nos ambulatórios de doenças infecciosas do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
1
5
0
7
Order By: Relevance
“…They also found adverse drug reactions (ADRs) at the beginning of treatment was another reason for poor or non-adherence. Corroborating, Cancian et al (2015) found that of the 90 registered non-adherent patients, only 39 attended the multiprofessional consultations, where one of the main factors for non-adherence reported by them were the gastrointestinal adverse effects. Cancian et al (2015) also found that most of the research participants are age group above 27 years old, with females prevailing, showing that women are more concerned in terms of health care than men, and as found in previous studies, part of the patients (56.41%) had a low level of education, of which, according to the authors, is a factor that led patients to abandon ART in the beginning.…”
Section: Difficulty In Adhering To Antiretrovirals By Patients With Hmentioning
confidence: 97%
See 2 more Smart Citations
“…They also found adverse drug reactions (ADRs) at the beginning of treatment was another reason for poor or non-adherence. Corroborating, Cancian et al (2015) found that of the 90 registered non-adherent patients, only 39 attended the multiprofessional consultations, where one of the main factors for non-adherence reported by them were the gastrointestinal adverse effects. Cancian et al (2015) also found that most of the research participants are age group above 27 years old, with females prevailing, showing that women are more concerned in terms of health care than men, and as found in previous studies, part of the patients (56.41%) had a low level of education, of which, according to the authors, is a factor that led patients to abandon ART in the beginning.…”
Section: Difficulty In Adhering To Antiretrovirals By Patients With Hmentioning
confidence: 97%
“…In the survey, the authors observed that treatment with only one antiretroviral was not indicated, the majority was given by three (66.2%) or by four drugs (32.3%). Development, v. 9, n. 10, e1289108280, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8280 Similar to Cancian et al (2015), Morais, Oliveira and Costa (2014) noted that male patients go to the health services and have a low pharmacological adherence. The same authors identified that the prescribed therapeutic regimens are a factor that directly contributes to ART adherence, because a greater number of drugs used or prescribed can results in a lower continuous and correct use by patients.…”
Section: Difficulty In Adhering To Antiretrovirals By Patients With Hmentioning
confidence: 99%
See 1 more Smart Citation
“…In Santa Maria/RS, it was possible to observe that poor adherence to pharmacological treatment was mainly due to the low level of education and the lack of information on HIV patients. However, the performance of the multiprofessional team, which includes the pharmacist, allowed greater pharmacotherapeutic adherence of these patients (Cancian et al, 2015).…”
Section: Literature Revisionmentioning
confidence: 99%
“…Nonetheless, if adherence to treatment is not high enough for ART to be effective, all this investment may be jeopardized since the irregular use or the insufficient number of doses may lead to the development of resistant HIV viruses 28,29 . Thus, we must highlight the importance of this study, as the constant monitoring of adherence to ART in different regions of the country can direct the government's actions so that the investment is not jeopardized.…”
mentioning
confidence: 99%